New data on the natural history and description of the immatures of Fulgeochlizus bruchi, a bioluminescent beetle from Central Brazil (Elateridae, Pyrophorini) - Simone Policena Rosa; Cleide Costa; Neide Higashi (Papéis Avulsos de Zoologia, 2010)
The mature larva and pupa of Fulgeochlizus bruchi (Candèze, 1896) are described and illustrated. Bioluminescent patterns are also given. Comments, new data on the first instar larva and natural history data are presented. The first instar larvae differ from the mature larvae mainly in their chaetotaxy, which is sparse and more symmetrically distributed. Larva madura e pupa de Fulgeochlizus bruchi (Candèze, 1896) são descritas e ilustradas. Padrões de bioluminescência observados em laboratório são descritos. Comentários e novos dados sobre a larva de primeiro ínstar e de história natural são apresentados. As larvas de primeiro ínstar diferem das larvas maduras principalmente por sua quetotaxia, que é mais esparsa e mais simetricamente distribuída.